(untitled) (Bangladesh Journal of Scientific Research, 2018)
Petrography of the Neogene mudrocks in this study incorporates laser particle size analysis, thin sections and scanning electron microscopy (SEM). Ten representative mudrock samples were collected from outcrops of the Sitakund structure. From the studies, it is evident that mudrocks of Sitakund structure are characteristically silty. The silt content, as estimated by laser grain size analysis, of the mudrocks ranges from 39 to 77% with average of 58%. Significant amount of granular silt with the platy clay minerals is also evident from the SEM micrographs. The silts are mainly quartz, feldspar and micas. The high silt content in the Neogene mudrocks implies an enormous flux of silty sediments with a very high rate of sedimentation allowing little time for a more selective sorting. This supports the geologic history that the uplifting and erosion of Himalaya was at the peak during Miocene and the Ganges mega delta received highest rate of sedimentation and growth rendering shale consistently silty. Bangladesh J. Sci. Res. 30(1&2): 35-43, December-2017